Evaluasi Kebijakan Pelayanan e- KTP Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Bojonegoro - Arysyahdi, Rattih; Priyanto (Soetomo Magister Ilmu Administrasi, 2023)
Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bojonegoro or commonly referred to as Disduk Capil Kabupaten Bojonegoro is a public service office/agency in the field of population registration and civil registration. The Bojonegoro Regency Population and Civil Registration Office or commonly referred to as Disduk Capil of Bojonegoro Regency is a public service office/agency in the field of population registration and civil registration. This type of research uses qualitative research, descriptive research type aims to provide a systematic, factual and accurate description or explanation of the Quality of Service in the e-KTP Issuance System at the Bojonegoro Regency Population and Civil Registration Office. The result The three elements of e-KTP making services are the 3 (three) lowest service element values available at the Bojonegoro Regency Population and Civil Registration Office and are included in the "GOOD" performance category. Community satisfaction with the service of e-KTP making services at the Population and Civil Registration Office is 3.33 with a conversion value of 83.35, where this value is included in the "GOOD" category In general, the overall quality of public service elements at the Bojonegoro District Population and Civil Registration Office is "GOOD". Keywords: public policy, policy evaluation, e-KTP